A review of the genera comprising species of the genus Eurynogaster sensu Hardy & Kohn, 1964 in Hawai'i (Diptera: Dolichopodidae) - Evenhuis, Neal L. (Zootaxa, 2005)
The generic limits are redefined for the endemic Hawaiian dolichopodid genera Eurynogaster Van Duzee, Sweziella Van Duzee, and Uropachys Parent, with the latter two resurrected from synonymy with Eurynogaster. Additionally, four new endemic Hawaiian genera are described: Arciellia, gen. n., Adachia, gen. n., Elmoia, gen. n., and Major, gen. n., to accommodate species previously placed in Eurynogaster. The related genus Sigmatineurum is redefined. Based on re-examination of male genitalic and other diagnostic characters and study of type material, a number of species previously placed in Eurynogaster are transferred to the other genera producing the following new combinations: Sweziella aeruginosa (Hardy & Kohn), comb. n., S. conspicua (Hardy & Kohn), comb. n., S. emarginata (Hardy & Kohn), comb. n., S. gracilipennata (Hardy & Kohn), comb. n.,S. pictilipenna (Tenorio), comb. n., S. tergoprolixa (Hardy & Kohn), comb. n., S. virida (Van Duzee), comb. n., Uropachys clavastylus (Hardy & Kohn), comb. n., U. crassicercus (Hardy & Kohn), comb. n., U. flavicrurus (Hardy & Kohn), comb. n., U. fusticercus (Hardy & Kohn), comb. n., U. palustricola (Hardy & Kohn), comb. n., U. pulvereus (Hardy & Kohn), comb. n., Arciellia dolichostoma (Hardy & Kohn), comb. n., A. flaviventer (Hardy & Kohn), comb. n., A. xanthopleura (Hardy & Kohn), comb. n., Adachia apicenigra (Van Duzee), comb. n., A. hispida (Hardy & Kohn), comb. n., A. nigripedis (Hardy & Kohn), comb. n., A. nudata (Hardy & Kohn), comb. n., A. williamsi (Hardy & Kohn), comb. n., Elmoia bullata (Hardy & Kohn), comb. n., E. exartema (Hardy & Kohn), comb. n., E. hamata (Hardy & Kohn), comb. n., E. lanceolata (Tenorio), comb. n., E. multispinosa (Hardy & Kohn), comb. n., E. nigrohalterata (Parent), comb. n., E. saxatilis (Grimshaw), comb. n., E. viridifacies (Parent), comb. n., and Major minor (Parent), comb. n. E urynogaster parenti Hardy & Kohn is synonymized with Pachyurus hawaiensis Parent, syn. n., which is removed from secondary homonymy with Eurynogaster hawaiiensis (Grimshaw) and returned to Uropachys, rev. stat. A key to the genus Eurynogaster and allies in the Hawaiian Islands is included.